Pengaruh Pelatihan Tata Boga terhadap Minat Berwirausaha di Balai Latihan Kerja (BLK) Kabupaten Temanggung - Cita Aura Pristiyan; Hendra Dedi Kriswanto (Pusat Riset dan Inovasi Nasional, 2025)
The surge in unemployment in Indonesia is a serious challenge that demands strategic and sustainable solutions. One approach that is gaining increasing attention is the development of entrepreneurship, particularly through skills training that can be directly applied in the workplace. This study focuses on analyzing the extent to which culinary training organized by the Temanggung Regency Vocational Training Center (BLK) can influence the entrepreneurial interest of its participants. This study uses a quantitative approach with an associative research design that aims to examine the causal relationship between culinary training variables and entrepreneurial interest. The research sample consisted of 32 respondents selected from culinary training participants at the Temanggung BLK. Data were collected through a structured questionnaire and analyzed using simple linear regression analysis techniques. The results show that culinary training has a positive and significant influence on increasing entrepreneurial interest. This is evidenced by a significance value of 0.005, which is below the threshold of 0.05, so the relationship between the two variables can be said to be statistically significant. In addition, the correlation coefficient (R) of 0.481 indicates a positive relationship with moderate strength. This means that the better the implementation of culinary arts training, the higher the participants' interest in becoming entrepreneurs in the culinary field. Quantitatively, the contribution of culinary arts training to increasing entrepreneurial interest reached 48.1%, as indicated by the coefficient of determination (R²). Meanwhile, the remaining 51.9% was influenced by factors other than training, such as family background, personal motivation, access to business capital, social environment, and support from government policies and financial institutions. These findings indicate that practical skills training such as culinary arts not only provides technical knowledge but also can shape an entrepreneurial mindset among participants.